Involvement of the Bacillus SecYEG Pathway in Biosurfactant Production and Biofilm Formation - Okouakoua, Frédéric Yannick; Kayath, Christian Aimé; Mokemiabeka, Saturnin Nicaise; Moukala, David Charles Roland; Kaya-Ongoto, Moïse Doria; Nguimbi, Etienne (International Journal of Microbiology, 2024)
With Bacillus species, about 30% of extracellular proteins are translocated through the cytoplasmic membrane, coordinated by the Sec translocase. This system mainly consists of the cytoplasmic ATPase SecA and the membrane-embedded SecYEG channel. The purpose of this work was to investigate the effects of the SecYEG export system on the production of industrial biomolecules, such as biosurfactants, proteases, amylases, and cellulases. Fifty-two isolates of Bacillus species were obtained from traditional fermented foods and then characterized using molecular microbiology methods. The isolates secreted exoenzymes that included cellulases, amylases, and proteases. We present evidence that a biosurfactant-like molecule requires the SecA ATPase and the SecYEG membrane channel for its secretion. In addition, we showed that biomolecules involved in biofilm formation required the SecYEG pathway. This work presents a novel seven-target fragment multiplex PCR assay capable of identification at the species level of Bacillus through a unique SecDF chromosomal gene. The bacterial membrane protein SecDF allowed the discrimination of Bacillus subtilis, B. licheniformis, B. amyloliquefaciens, and B. sonorensis. SecA was able to interact with AprE, AmyE, and TasA. The Rose Bengal inhibitor of SecA crucially affected the interaction of AprE, AmyE, TapA, and TasA with recombinant Gst-SecA. The Rose Bengal prevented Bacillus species from secreting and producing proteases, cellulases, amylases, and biosurfactant-like molecules. It also inhibited the formation of biofilm cell communities. The data support, for the first time, that the SecYEG translocon mediates the secretion of a biosurfactant-like molecule.